Development of Armenian Social and Sociological thought: Brief Historical Overview - Gevorg Poghosyan (Recent Research Advances in Arts and Social Studies Vol. 5, 2024)
The chapter represents the issues of the origin and evolution of social thought and sociological researches in Armenia. The process of the emergence of social and sociological thoughts in Armenia considered from the early Middle Ages to the beginning of the 20th century. Since the ancient period Armenian philosophers in their works addressed the problems of man and his environment, social relations and the role of the state. In scholarly publication it is customary to draw a distinction between sociological ideas, conceptual frameworks and theories, on the one hand, and applied social studies, on the other hand.